Changing climate - Changing livelihood: Smallholder's perceptions and adaption strategies. (1st April 2020) - Funk, Christoph; Raghavan Sathyan, Archana; Winker, Peter; Breuer, Lutz
Abstract: Experts expect that climate change will soon have a severe impact on the lives of farmers in the region surrounding Kerala, India. This region, which is known for its monsoon climate (which involves a distinct temporal and spatial variation in rainfall), has experienced a decrease in annual rainfall over the last century. This study is aimed at investigating how smallholder farmers perceive climate change and at identifying the methods that these smallholders use to adapt to climate change. We use data collected from a survey of 215 households to compare the climate vulnerability of three watershed communities in Kerala. We find that the farmers perceive substantial increases in both temperature and the unpredictability of monsoons; this is in accordance with actual observed weather trends. The selection of effective adaptation strategies is one of the key challenges that smallholders face as they seek to reduce their vulnerability. The surveyed households simultaneously use various adaptation methods, including information and communication technology, crop and farm diversification, social networking through cooperatives, and soil and water conservation measures. The results of a binary regression model reveal that the household head's age, education and gender, as well as the farm's size and the household's size, assets, livestock ownership, poverty status and use of extension services, are all significantly correlated with the households' choices regarding adaptations to cope with climate change. Highlights: Households perceive an increase in average temperature, hot months and rainfall. Various factors significantly affect the adaptation strategies used by households. Experienced farmers are less likely to seek social assistance and to use irrigation methods. Male-headed households are more likely to use new technologies and farming practices. Women's participation are more likely in social activities and attendance of meetings.